FAKTOR YANG BERHUBUNGAN DENGAN KEPATUHAN PENGGUNAAN ALAT PELINDUNG DIRI PEKERJA KEBERSIHAN LIMBAH MEDIS RSUD PASAR MINGGU - Febrianti Nasaindah Zuchri (2023)
Janitors are at risk of exposure to biohazards and disease due to the work they do. This risk can increase if workers do not complsy with using complete personal protective equipment. Various factors can be associated with workers' compliance with using personal protective equipment. This study aims to determine the factors associated with adherence to personal protective equipment for medical waste janitors at RSUD Pasar Minggu. This research is a cross-sectional study using a total sample, which means that the research subjects are all medical waste janitors at RSUD Pasar Minggu, with a total of 93 respondents. Data collection used a modified questionnaire from the previous research questionnaire and was tested for validity and reliability. Data analysis used univariate analysis, and bivariate analysis used the chi-square test. The analysis results show a significant relationship between age, years of service, knowledge, attitudes, availability of PPE, and supervision with adherence to PPE. Education and condition factors have no relationship with adherence to PPE. It is suggested that the RSUD Pasar Minggu can provide outreach to increase worker understanding regarding the use of PPE and improve supervision by monitoring and evaluating compliance with the use of PPE for medical waste janitors.